2019 IEEE Wireless Communications and Networking Conference (WCNC) 2019
DOI: 10.1109/wcnc.2019.8885416
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Resource Allocation for Secure UAV Communication Systems

Abstract: In this paper, we study the resource allocation and trajectory design for energy-efficient secure unmanned aerial vehicle (UAV) communication systems where a UAV base station serves multiple legitimate ground users in the existence of a potential eavesdropper. We aim to maximize the energy efficiency of the UAV by jointly optimizing its transmit power, user scheduling, trajectory, and velocity. The design is formulated as a nonconvex optimization problem taking into account the maximum tolerable signal-to-nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…In our simulations, we compare the system energy efficiency of the proposed algorithm "PA", with the other three baseline schemes: (a) No jammer UAV (NJ), which has only an information UAV in this scheme. The suboptimal resource allocation and UAV's trajectory for "NJ" can be obtained by using a similar approach as in our previous work [1]. (b) Single-antenna jammer UAV (SAJ), in which both the information UAV and jammer UAV are all equipped with a single-antenna to provide secure communication.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our simulations, we compare the system energy efficiency of the proposed algorithm "PA", with the other three baseline schemes: (a) No jammer UAV (NJ), which has only an information UAV in this scheme. The suboptimal resource allocation and UAV's trajectory for "NJ" can be obtained by using a similar approach as in our previous work [1]. (b) Single-antenna jammer UAV (SAJ), in which both the information UAV and jammer UAV are all equipped with a single-antenna to provide secure communication.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Since "SLI" is another subcase of the problem formulation for "PA", the suboptimal solution can be obtained by optimizing resource allocation with fixing the information UAV's trajectory. Since the initial information-UAV trajectory will affect the performance of the proposed suboptimal solution, we have tried different reasonable trajectories as an initial point, e.g., (1) Straight forward flight from the initial point to the destination (SFF); (2) A path passing through all users' location once;…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our simulation, we compare the performance of the proposed algorithm, denoted as PA with the other two baseline schemes: a) No jammer (NJ), which all UAVs serve as information UAV and do not transmit artificial noise to eavesdroppers [14]- [16]. Since the problem for PA subsumes the NJ scheme as a subcase, the average minimum secrecy rate per user in NJ can be achieved by solving subproblem 1 and subproblem 3 with the settings of jamming power as zero.…”
Section: Overall Algorithmmentioning
confidence: 99%
“…In [16], the authors have studied PLS of a UAV-enabled mobile relaying scheme over non-fading AG channels, and showed that moving buffer-aided relay provides significant performance over static relaying in terms of secrecy rate. In [17], the authors studied the resource allocation and path-planning problem for energy-efficient secure transmission from a UAV base station to multiple users in the presence of a passive ground eavesdropper. In [18], employing UAV as a friendly jammer to enhance PLS of a ground-relaying based communication has been studied.…”
Section: Introductionmentioning
confidence: 99%